Enhancing Local Coffee Business Competitiveness through Production Improvement and Marketing Digitalization at Kedai Titik Anggur, North Lombok - Lale Puspita Kembang; Lalu Delsi Samsumar; Dewi Rispawati; Ni Wayan Adelia Mutiara Asri (Pascasarjana Universitas Mataram, 2025)
Kedai Kopi Titik Anggur, a potential micro-enterprise in Sesait Village, North Lombok, faces significant operational hurdles due to traditional manual production methods and a marketing scope confined strictly to the local vicinity. These limitations have resulted in inconsistent product quality and restricted sales growth. This community service program aims to elevate the partner's competitiveness through comprehensive production management optimization and digital marketing transformation. The implementation utilized a participatory approach encompassing five systematic stages: socialization, technical training, appropriate technology adoption, intensive mentoring, and impact evaluation. Technological interventions focused on standardizing quality through the deployment of automatic roasting machines with precision temperature control, digital grinders, and vacuum packaging to extend shelf life. Simultaneously, market expansion was driven by developing a private e-marketplace website integrated with digital payment systems and optimizing social media branding. The outcomes were substantial: daily production capacity surged by 50-60%, production lead time was reduced by 25%, and product quality inconsistency dropped by 30%. Economically, total sales volume grew by 28% within the first three months, with the newly established online channel contributing 35% to the revenue. These findings confirm that integrating modern production technology with digital marketing strategies effectively enhances operational efficiency, market access, and long-term business sustainability.